Contemporary Business Ethics: Navigating Moral Challenges in the Modern Corporate World - Sari, Euis Ayu Indah Purnama; Sikki, Nurhaeni; Budiawan, Likha Navadiani; Mandala, Nesha Adelina; Naja, Nadia Syahran (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This journal explores contemporary business ethics, examining the evolution of moral principles within modern corporate settings. Through literature analysis and case examples, it delves into key issues such as corporate social responsibility (CSR), stakeholder theory, environmental ethics, digital privacy, and ethical leadership. The paper emphasizes the importance of ethical decision-making in sustaining competitive advantage, corporate reputation, and long-term profitability.